Phenotypical and molecular landscape of B lymphocytes in patients with Intrahepatic Cholangiocarcinoma. (March 2023) - Milardi, G.; Franceschini, B.; Camisaschi, C.; Costa, G.; Soldani, C.; Uva, P.; Cassani, B.; Lleo, A.
Abstract : Intrahepatic cholangiocarcinoma (iCCA) is a heterogeneous biliary tract cancer whose incidence is rising worldwide. Due to the aggressive evolution of the disease, there is an urgent need for diagnostic and therapeutic alternatives. The immune infiltrate, key component of the tumor microenvironment (TME), remains poorly characterized, limiting development of successful immunotherapies. Herein, we aimed to define phenotypical and molecular characteristics of B lymphocytes, whose role in iCCA development is still controversial. Single-cell RNA-sequencing analysis of CD20 + cells in iCCA patients identified four main subclusters of B and revealed a downregulation of B cell activation/inflammatory genes in intratumoral compared to adjacent non-malignant tissue, suggesting that B cells play a protective role in iCCA progression. Multicolor flow cytometry analysis demonstrated an abundant infiltration of immature naïve B cells respect to the memory phenotype. A reduction in B-cell effector functions was also detected, probably due to the cellular components of the TME. Immunohistochemical analyses showed that B cells, when infiltrate the tumor tissue, create cellular aggregates similar to tertiary lymphoid structures. Overall, these observations suggest that iCCA tissue may contain various B cells subtypes with protective role, probably limited by TME. However, a comprehensive characterization of B cell property, organization and crosstalk with other cells of iCCA milieu will elucidate mechanisms of tumor progression or control, exploitable for the development of novel immunotherapeutic approaches. The present work was partially funded by the Associazione Italiana per la Ricerca sul Cancro (IG AIRC 2019 – ID 23408 to A. Lleo)